Meta-analysis of cryoablation versus radiofrequency ablation in the treatment of malignant liver tumors - Xiangzhong Huang; Xinjian Xu; Hongtao Du; Qiulian Sun; Minyu Wu (International Journal of Hyperthermia)
Objective A meta-analysis was conducted to assess the efficacy and safety of cryoablation (CRA) compared with radiofrequency ablation (RFA).Methods A systematic search of PubMed, EMBASE, Cochrane Library, Wanfang, CNKI, and VIP databases was conducted to identify clinical controlled studies comparing CRA versus RFA for hepatic malignancies up to July 2022. The meta-analysis was performed using RevMan 5.3.Results A comprehensive analysis was conducted on 8 clinical controlled studies involving a total of 943 patients. There were no significant differences in the incidence of complications, complete ablation of lesions, local recurrence, and 1-year survival between the CRA and RFA groups (OR = 0.98, 95%CI: 0.61–1.55, p = 0.92; OR = 1.08, 95%CI: 0.62–1.90, p = 0.78; OR = 1.28, 95%CI: 0.49–3.36, p = 0.61; and OR = 1.14, 95%CI: 0.63–2.06, p = 0.66, respectively).Conclusion The efficacy and safety profile of CRA was comparable to that of RFA in the context of ablation therapy for hepatic malignancies. These findings suggested that CRA may be a valuable alternative to RFA in the treatment of hepatic malignancies.